2009
DOI: 10.1021/jf901070g
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Natural Functional Ingredients from Microalgae

Abstract: Nowadays, a wide variety of compounds such as polyphenols, polyunsaturated fatty acids (PUFA), or phytosterols obtained, for example, from wine, fish byproducts, or plants are employed to prepare new functional foods. However, unexplored natural sources of bioactive ingredients are gaining much attention since they can lead to the discovery of new compounds or bioactivities. Microalgae have been proposed as an interesting, almost unlimited, natural source in the search for novel natural functional ingredients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(234 citation statements)
references
References 153 publications
4
221
0
4
Order By: Relevance
“…Spirulina is high in unsaturated and polyunsaturated fatty acids in particular (25% -60% of the total fatty acids), such as oleic acid, linoleic acid, gamma-linolenic acid and docosahexaenoic (DHA) (Hue et al, 2002;Yukino et al, 2005;Habib et al, 2008). It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Spirulina is high in unsaturated and polyunsaturated fatty acids in particular (25% -60% of the total fatty acids), such as oleic acid, linoleic acid, gamma-linolenic acid and docosahexaenoic (DHA) (Hue et al, 2002;Yukino et al, 2005;Habib et al, 2008). It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Such foods are named functional foods or nutraceuticals, a concept that was born in Japan early in 1980 (Plaza et al, 2009;Christaki et al, 2011;Borowitzka, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorella vulgaris is unicellular green algae, broadly used as a food supplement and it has high antioxidant and therapeutic uses such as lutein, α, β-carotene, ascorbic acid and α-tocopherol, which are active against free radicals and may be responsible for Chlorella functional activities [36,37]. Furthermore, α and β-carotene in C. vulgaris not only react with various ROS but also interfere with the processes of oxidation in the lipid and cellular compartment [38].…”
Section: (Handex1000) C: Liver Tissue Section Of Rats Treated With Delmentioning
confidence: 99%
“…Wound healing: These last years, researchers speculate that the minerals, phycobiliproteins, vitamins, beta-carotene, fatty acids, polysaccharides, phenolic compounds and volatile compounds present in these microalgae may accelerate wound healing by acting as an antioxidant and scavenging destructive free radicals responsible for cell death (Qishen et al, 1988;Kim et al, 1998;Hirahashi et al, 2002;Reddy et al, 2003;Subhashini et al, 2004;Li et al, 2005;Patel et al, 2005;Singh et al, 2005;El-Baky et al, 2009;Plaza et al, 2009). These reports confirmed that some unidentified factors in the crude extract might have enhanced the healing process.…”
Section: Mode Of Administrationmentioning
confidence: 99%